Metal–Organic Frameworks (MOF)-Derived Gel Electrolyte via UV Cross-Linking for High-Performance Lithium Metal Batteries - Naiyao Mao; Lingxiao Lan; Qiankun Hun; Jianghua Wei; Xinghua Liang; Yifeng Guo (Gels)
Gel electrolytes (GEs) play a pivotal role in the advancement of lithium metal batteries by offering high energy density and enhanced rate capability. Nevertheless, their real-world application is hampered by relatively low ionic conductivity and significant interfacial resistance at room temperatures. In this work, we developed a gel electrolyte membrane (GEM) by embedding Zeolitic Imidazolate Framework-8 (ZIF-8) metal–organic frameworks (MOFs) material into a poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) matrix through UV curing. The composite membrane, with 4 wt% ZIF-8, exhibited an ionic conductivity of 1.17 × 10−3 S/cm, an electrochemical stability window of 4.7 V, and a lithium-ion transference number of 0.7. The test results indicate that the electrochemical performance of LFP//GEM//Li battery has an initial specific capacity of 168 mAh g−1 at 0.1 C rate. At 1 C, the discharge capacity was 88 mAh g−1, and at 2 C, it was 68 mAh g−1. Enhanced ionic transport, improved electrochemical stability, and optimized lithium-ion migration collectively contributed to superior rate performance and prolonged cycle life. This study offers novel insights and methodological advances for next-generation lithium metal batteries technologies.